2008
DOI: 10.1177/0003319708322388
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Low-Intensity Pain-Free Treadmill Exercise on Functional Capacity of Individuals Presenting with Intermittent Claudication Due to Peripheral Arterial Disease

Abstract: Patients with intermittent claudication due to peripheral arterial disease (PAD) experience muscle aching during walking secondary to ischemia. The purpose of this study was to examine the effects of low-intensity pain-free exercise (LIPFE) on functional capacity of individuals with PAD. A total of 12 participants with PAD underwent training on treadmill for 6 weeks, twice a week, for about 45 minutes. Outcome measures included walking distance (WDI), walking duration (WDU), mean walking rate (WR), estimated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Therefore, the analysis was further restricted to only the participants that participated for 10-14 weeks, comparing performance based on gender using pooled data reported from previous studies. 3,[26][27][28][29][30] …”
Section: Methods Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the analysis was further restricted to only the participants that participated for 10-14 weeks, comparing performance based on gender using pooled data reported from previous studies. 3,[26][27][28][29][30] …”
Section: Methods Participantsmentioning
confidence: 99%
“…3,[26][27][28][29][30] The protocol (see Figure 1) consists of having participants walk on a treadmill (Model 2000, Star Trac Treadmill, Unisen Inc, Tustin, CA) for 30 to 50 min two days per week, below the participant's minimal pain threshold (defined as a score of 0.5 to 1 on the IC Pain Scale, see Table 1). 3,[26][27][28][29][30] When participants felt IC pain, the speed of the treadmill was reduced by approximately 0.80 km with participants continuing to walk until the pain subsided. The patients would not stop unless they were at the minimum speed on the treadmill and a lower speed was not possible.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activity/walking is recommended in patients with PAD. It has been shown that regular exercise has an important beneficial impact on functional capacity and the prevention of PAD and CAD, particularly through the beneficial effects on endothelial function, antioxidant systems, heatshock protein expression, and vascular remodeling [12,13] . Supervised physical training, besides being the most effective means to increase walking ability, also proved to have a benefit on LV contractility.…”
Section: Discussionmentioning
confidence: 99%
“…An 8-week program with 3 exercise sessions per week features a pain-free, symptom-responsive, low intensity treadmill protocol. 20 This effort includes additional objective and quality-of-life evaluations that are lacking in this current retrospective report. Specifically, objective measures such as maximal walking distance, walking duration, mean walking rate, estimated oxygen consumption, metabolic equivalents, estimated total energy expenditure, and estimated rate of energy expenditure are incorporated at intervals throughout the program.…”
Section: Discussionmentioning
confidence: 99%